There's an App for That: Using Geosocial Networking Apps to Access Young Black Gay, Bisexual, and other MSM at Risk for HIV. Issue 1 (January 2020) - Fields, Errol L.; Long, Amanda; Dangerfield, Derek T.; Morgan, Anthony; Uzzi, Mudia; Arrington-Sanders, Renata; Jennings, Jacky M.
Purpose: Young black gay, bisexual, and other MSM (YBMSM) that carry a disproportionate HIV burden in the US Geosocial networking applications (GSN apps) are environments that may increase HIV risk among users. This study explored the acceptability and feasibility of using these apps for HIV/sexually transmitted infection (STI) public health outreach. Design: Semi-structured in-depth qualitative interviews. Setting: A frequently reported GSN app for meeting sex partners by newly diagnosed HIV-infected MSM in Baltimore. Participants: Seventeen YBMSM aged 18 to 24 (mean = 21.5/SD = 1.8) who were logged-on to the GSN app in venues or census tracts in high HIV transmission areas. Methods: Participants completed 60 to 90 minute semi-structured interviews, which were audio-recorded and transcribed. Interview data were analyzed in NVivo10 using categorical analysis and double-coded until consistency was achieved. Results: Participants described GSN apps as acceptable and feasible resources for public health practitioners seeking to access YBMSM to provide HIV/STI treatment and prevention services and resources. Three themes emerged: (1) the need to authenticate public health messages to distinguish from spam; (2) improved access to YBMSM including opportunities to identify and access virtual congregations of youth in non-gay-related spaces; and (3) the importance of avoiding stigmatizing YBMSM when targeting sexual health messages. Conclusion: GSN apps have great potential as tools for identifying and engaging at-risk YBMSM. Additional work is needed to understand limitations of this medium, to develop strategies to engage YBMSM without further stigmatizing them, and to maximize their outreach potential.